Black pearl carbon as a catalyst for all-vanadium redox flow batteries. Issue 69 (8th August 2019) - Sodiq, Ahmed; Mohapatra, Lagnamayee; Fasmin, Fathima; Mariyam, Sabah; Arunachalam, Muthumeenal; Kheireddine, Aziz; Zaffou, Rachid; Merzougui, Belabbes
Abstract : We report for the first time, the performance of black pearl (BP) carbon as an electrocatalyst in all-vanadium redox-flow-batteries. Abstract : We report for the first time, the performance of black pearl (BP) carbon as an electrocatalyst in all-vanadium redox-flow-batteries. Our results show significant suppression in peak potential separation (faster in kinetics than CNTs), 17% improvement in energy efficiency (when compared with CNTs) and good activity retention after 800 potential cycles.